Compensatory increase in oxygen extraction fraction is associated with age-related cerebrovascular disease - John McFadden; Julian Matthews; Lauren Scott; Karl Herholz; Ben Dickie; Hamied Haroon; Oliver Sparasci; Saadat Ahmed; Natalia Kyrtata; Geoffrey J.M. Parker; Hedley C.A. Emsley; Joel Handley; et al. (NeuroImage: Clinical)
Cerebrovascular disease is an important contributor to dementia with reductions in cerebral blood flow (CBF) potentially compromising oxygen supply. In early stages, reduced CBF may be associated with a compensatory increase in oxygen extraction fraction (OEF) to maintain the cerebral metabolic rate of oxygen consumption (CMRO2). We used a simultaneous PET-MRI protocol to measure OEF, CBF, CMRO2, and arterial transit time (ATT) in elderly people (n = 24, age 69.6 ± 5.3 years) with a range of vascular disease risk (QRisk 18.7 ± 10.8 %) and cognitive abilities (MoCA scores 26.7 ± 3.4) to determine if a) vascular disease risk (parameterised with QRisk2 score) is associated with altered CBF, ATT, OEF and CMRO2, b) if impaired blood supply and increasing transit times are associated with elevated OEF and c) if these physiological measures are associated with impaired cognition. ATT rose by 132 ms per 10 point increase in QRisk and there was a trend for reduced CBF. Compensatory increases in OEF occurred in association with modified ATT and CBF, preserving CMRO2. There was no regional variation to these relationships. Cognitive impairment was associated with prolonged ATT. These findings demonstrate the potential use of multi-delay time ASL and Quantitative Susceptibility Mapping for the early detection of cerebrovascular changes and provide evidence for compensatory increases in oxygen extraction in the presence of reduced blood flow.